Health Behaviors Among Students and Their Association with Stress, Student Burnout and Study Engagement - Nils Olson; Renate Oberhoffer; Barbara Reiner; Thorsten Schulz (Societies, 2025)
The prevalence of stress and burnout in higher education exceeds rates of the general working population, affecting students’ health and increasing university drop-out rates. Study engagement—a positive state of energy, dedication, and absorption—acts as a protective factor. A healthy lifestyle is neglected by many students, especially early in their studies. Since habits like diet, physical activity, weight management, and substance use impact mental health and resilience, their role in stress and burnout should be explored. In a cross-sectional online survey of 1955 German university students, sociodemographic data were collected and perceived stress, study engagement, and burnout were assessed. Associations with health habits, including diet, fitness, and tobacco and alcohol use, were examined. Physical activity was measured via the International Physical Activity Questionnaire, and alcohol consumption was measured via the Alcohol Use Disorders Identification Test. Among the students, 73.4% experienced moderate to high stress, with females reporting higher levels. Almost one-third had frequent burnout symptoms, while less than half (44.5%) reported high study engagement, with no sex differences. Active lifestyles, healthy diets, and fitness were linked to stress, burnout, and engagement. Perceived fitness and diet had the strongest associations with stress (d = 0.198–0.906), burnout (d = 0.277–0.483), and engagement (d = 0.218–0.272), while BMI (d = 0.089–0.186), sitting hours (d = 0.172–0.203), and physical activity (d = 0.096–0.141) played a comparatively minor role, regarding their small effect size. Personal habits are significantly linked to burnout and engagement, possibly by enhancing resilience. Health literacy regarding study demands is key for effective prevention and targeted student health management. More objective fitness data could further validate these findings.